Oral administration of bone marrow-derived mesenchymal stem cells attenuates intestinal injury in necrotizing enterocolitis - Yeong Seok Lee; Yong Hoon Jun; Juyoung Lee (The Korean Pediatric Society, 2024)
Background Necrotizing enterocolitis (NEC) is a major cause of morbidity in premature infants. However, effective treatment options for NEC are currently lacking. Purpose This study aimed to determine the optimal dose of intraperitoneally administered bone marrow-derived mesenchymal stem cells (BM-MSCs) and investigate the therapeutic potential of orally administered BM-MSCs in NEC. Methods Neonatal mice were fed maternal breast milk for the first 2 days of life. On day 3, the neonatal mice were randomly divided into control, negative control, and BM-MSC-treated groups. Lipopolysaccharide (LPS) was administered for 3 days, and cold stress (4°C, 10 minutes) was applied 3 times a day to induce NEC. High-dose (1×106 cells) or low-dose (1×105 cells) BM-MSCs were administered intraperitoneally 1 or 3 times between days 6 and 8 to treat the NEC. The orally administered group received a low dose of BM-MSCs on day 6. Furthermore, except for the control group, intraepithelial cells (IECs) of the small intestine of neonatal mice were treated with LPS and exposed to 5% O2/95% N2 hypoxic stress for 2 hours. Thereafter, each was treated with BM-MSCs. Results Tissue injury, apoptosis, and inflammatory marker levels were significantly reduced after BM-MSC administration. Oral administration was as effective as intraperitoneal administration, even at a low dose (1×105 cells) of BM-MSCs. The efficacy of high (1×106 cells) or multiple divided doses of BM-MSCs did not differ from that of low-dose treatment. Significantly improved wound healing was observed after BM-MSC administration to injured IECs. Conclusion The oral administration of BM-MSCs is a promising treatment option for NEC in infants. Further human studies of BM-MSCs are necessary to determine the optimal dose required to achieve safe and effective outcomes.